(untitled) (ModaPalavra e-periódico, 2010)
This article analyses the fashion designer activity in contemporaneous society as one form of immaterial, cognitive and creative work insert of fashion industry. This article is result of documental and bibliography research. It use in articulated form the analytic tools of sociology of work, sociology of fashion and economic sociology specialized in networks analyses. The article concluded that the works of fashion designer constitute one productive activity of immaterial, cognitive and creative dimension that demand multiples abilities.